Czech Public Attitudes to the Chemical Industry - Lošťáková, Hana; Jelínková, Martina; Ostřanský, Filip (Česká společnost průmyslové chemie, 2017)
In the today's challenging and dynamic market environment, it is not enough to provide customers with a wide range of high quality products, but it is also necessary to develop intangible benefits for customers, especially a comprehensive range of high quality services and partnership-based relations. Very important is a supplier's reputation as a solid business partner, too. Corporate reputation is primarily based on the reputation of the entire industry, not only for customers, but for the wider public. This paper summarizes the theoretical background regarding the sector's reputation and summarizes the results of a primary quantitative research focused on the perception of the position and importance of the chemical industry in the national economy of the Czech Republic. The research was conducted at the turn of 2016 and 2017 using personal interviews in the Czech population aged over 15 years on a sample of 1,364 respondents selected by quota sampling. The research has shown that the Czech public perceives the chemical industry as very beneficial to the national economy, almost at the same level as the pharmaceutical industry, automobile engineering, food and power industries. It is aware of the high usefulness of the chemical industry products for the humankind and for other industries, and the prospects of its future development resulting therefrom. It considers this sector to be a modern, dynamic one, offering a rather better salary package. To studying chemistry and the attractiveness of employment in the chemical industry, however, the Czech public attitudes are controversial, some positive, some negative. It is mainly due to the fact that the majority of the Czech population still considers this sector to be less safe, with poorer working conditions, less environmentally friendly, insufficiently supportive of social activities such as sport, culture and charity events.
Postoje české veřejnosti k chemickému průmyslu
Keywords: reputation; attitudes of Czech public; chemical industry; pověst; postoje české veřejnosti; chemický průmysl